NILAI PERSAHABATAN DALAM FILM YOWIS BEN 2 - Novansyah, Rendhy; hakim, lukman (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2023)
Friends are peers who participate in joint activities, support each other and share closeness. Stories are often the main plot in a film's storyline. The Yowis Ben film, which has a duration of 1 hour 49 minutes, is based on the Indonesian comedy-drama genre by Fajar Nugros and Bayu Skak, describing the journey of a local band based on the Javanese language in spreading their band name to the national realm. The purpose of this study is to find out how the views of the characters in the movie "Yowis Ben 2" about the values ​​of friendship. This study uses a qualitative research method with Roland Barthes' semiotic approach which is based on reasoning and meaning. The three basic parts of generation are supported by the Denotation, Connotation, and Myth models. The results of this study indicate that the film "Yowis Ben 2" values ​​friendship, among others, caring, solidarity and cohesiveness.